Project characteristics and performance in Europe: An empirical analysis for large transport infrastructure projects. (April 2017) - Locatelli, Giorgio; Invernizzi, Diletta Colette; Brookes, Naomi J.
Highlights: Transport Infrastructure Projects (TIPs) are often over budget and late. This study investigates the correlation between project characteristics and performance. The identification of correlations allows a focused investigation on the causations. The paper is based on 30 European large Transport Infrastructure Projects. External and Internal stakeholders account for most of the correlations. Abstract: Infrastructure megaprojects are historically associated with poor delivery, both in terms of cost and schedule performance. Large Transport Infrastructure Projects (TIPs) are amongst the most controversial and are often delivered late, over budget, and providing less benefit than expected. While there is a growing theoretical body of literature addressing TIPs, empirical research is still required to determine which TIPs characteristics affect TIPs schedule & cost performance. This paper addresses this issue, applying an empirically-based methodology to a dataset of 30 European TIPs. The results highlight the importance of financial support from the government and the strong influence of both external and internal stakeholders, mainly in relation to their early engagement and to their nationality. Technological characteristics and the presence of Special Purpose Entities are also correlated with the TIPs performance. These key findings both support and contradict the literature, and are relevant for both policy makers and project managers during the decision-making process, planning and delivery of TIPs.